Advances in the Semi-Synthesis of Triterpenoids - Liao, Jin-Xi; Hu, Zhen-Ni; Liu, Hui; Sun, Jian-Song (Synthesis, 2021)
Recent achievements in triterpenoid semi-synthesis are discussed in this short review, which is divided into three parts according to the type of synthetic strategy being employed. These strategies include functionalization, modification of the carbon skeleton, and glycosylation. In the section on functionalization strategies, both functional group interconversions and new functional group installations on triterpenoid starting materials are described. The section on modification of the carbon skeleton is divided into three parts according to the tactic being applied, and incorporates rearrangement of the carbon skeleton, ring scission, and introduction of an additional heterocyclic ring. Meanwhile, in the section on glycosylation, notable achievements in the semi-synthesis of both natural and artificial triterpene saponins are discussed. Overall, the pivotal transformations that have brought about striking chemical structure variations of triterpenoid starting materials are highlighted herein, and it is hoped that this short review will provide inspiration to both established and new investigators engaged in this field of research. 1 Introduction2 Semi-Synthesis of Triterpenoids via Functionalization Strategies2.1 Functionalization of Rings with Functional Groups2.2 Functionalization of a Side Chain2.3 Functionalization of Rings without Existing Functional Groups 2.4 Functionalization of Angular Methyl Groups2.5 Functionalization of Angular Methyl Groups and Functional-Group-Free Rings2.6 Multisite Modifications3 Semi-Synthesis of Triterpenoids via C-Skeleton Modification Strategies3.1 Rearrangement Tactics3.2 Ring-Opening Tactics3.3 Additional Ring Introduction Tactics4 emi-Synthesis of Triterpenoids via a Glycosylation Strategy5 Conclusions and Outlook
Keywords: triterpenoids; semi-synthesis; functionalization; C-skeleton modification; glycosylation